Akulturasi Agama dan Budaya dalam Praktik Ritual Kebaharian Masyarakat Misool Raja Ampat - Diah Aghsari; Ismail Suardi Wekke (Jurnal Airaha, 2015)
Religious ritual contains religion, culture and marine on Misool society. Among them is sea sasi. This ritual was conducted to maintain marine sustainability. Therefore, on the certain time they don’t harvest any kind of reosurces such as bia kapa, and other fishes. This practise shows aculturation between religion and tradition that choosen mostly on Misool Society. The dynamic encompass to sea sasi. This research findings shows Misool society extend the sasi as a must on certain periodical activities. It regulates before and after harvest time, around six months duration. Sea sasi ritual actually exited before Islam that perfomed for the God. Unfortunately, after Islam coming to the area, this culture aculturate and Islam is a contain of the acyivities such prophet praying, certain islamic ceremony. In addition, there is not any suspicios to present for the God because only Allah that have a right to request and pray for nowadays.